Pengaruh Brand Ambassador dan Product Review terhadap Keputusan Pembelian Online yang Dimediasi oleh Citra Merek bagi Konsumen Perempuan di Yogyakarta - Nabila Rama Yunita; Andriya Risdwiyanto (Jurnal Manajemen Strategis: Jurnal Mantra, 2024)
This research aims to determine the influence of brand ambassadors and product reviews on online purchasing decisions mediated by brand image for female consumers in Yogyakarta. The population in this study were female consumers who had used Scarlett Whitening products at least once. This study uses a quantitative approach. The sample used was non-probability sampling with a purposive sampling technique whose samples were based on certain criteria with a minimum sample of 80 respondents. This research uses questionnaire distribution data with the Google form. The data analysis tool used is Partial Least Square (PLS) with the SmartPLS version 3.0. Analytical tools are used to test data such as validity testing, reliability testing, hypothesis testing, and mediation testing. The results of this research show the significant influence of product reviews on online purchasing decisions, brand ambassadors on brand image, product reviews on brand image, and brand image on online purchasing decisions for Scarlett Whitening products for female consumers in Yogyakarta. Other findings show that brand ambassadors do not have a significant influence on online purchasing decisions. The mediation testing in this research shows that brand image is able to mediate brand ambassadors and product reviews on online purchasing decisions.